Editorial note. (22nd October 2018) - MITKOV, RUSLAN
Abstract : Our passion to continually improve the journal and, as a result, our contribution to the community drives our quest for highly diversified and up-to-date content. We are launching a new category of papers, i.e., 'keynote' or 'invited' papers, which will be penned by leading lights in the field.